Molecular Conformation and Thermal Diffusivity by Temperature Wave Analysis of Electric Polarized Biaxially Stretched Polyethylene Terephthalate Films - Satoto, Rahmat; Nugroho, Pramono (LIPI Press, 2009)
Structural and conformation of biaxially polyethylene terephthalate (PET) films after being polarized by electricfield was characterized using Fourier transform infrared (FTIR). The 950 kV/cm electric field was applied during the sample heating and cooling at 28-100-28oC. The electric field was directed to the sample thickness. Thermal diffusivity of the polarized PET films in the thickness direction was characterized using temperature wave analysis (TWA) as a function of temperature. An orientation function of 1719 cm-1 band which was assigned to a permanent dipole of C=O, shows an increasing orientation with the increase of polarization field. Thermal diffusivity also increased with the increasing of electric polarization field. The orientation function of 1340, 971 and 847 cm-1 bands did not show a clear tendency due to the polarization field. The correlation of molecule conformation change and thermal diffusivity in the biaxially stretched PET films is discussed.